Impact of hormonal contraceptives and hormone replacement therapy on gastrointestinal health: a comprehensive review - Manchikalapati, Aikya; Kataveni, Suhas; Pagidipally, Alekhya; Avvaru, Moksha P. (International Journal of Research in Medical Sciences, 2025)
Hormonal contraceptives and hormone replacement therapy (HRT) are widely used worldwide. While benefits are well established, exogenous hormones can affect the gastrointestinal (GI) system. These complications often nonspecific and delayed are underrecognized. In this review, we surveyed PubMed/MEDLINE/Embase through September 2025, assessing hormonal contraceptives or HRT in relation to GI/hepatobiliary outcomes. It was found that estrogen-containing contraceptives are most strongly linked to hepatocellular adenoma (HCA), with dose–duration dependence; lesions typically stabilize or regress after hormone withdrawal. Focal nodular hyperplasia showas no causal relationship and usually does not require contraceptive cessation once confidently diagnosed. Estrogen-induced cholestasis reflects down-regulation of canalicular transporters (e.g., BSEP, MRP2) and is more likely in genetically predisposed women, such as those with prior cholestasis of pregnancy. Estrogen increases biliary cholesterol; progestins reduce gallbladder contractility, together promoting lithogenesis – This effect is stronger with HRT than low dose combined contraceptives. Estrogen-associated pancreatitis occurs primarily via severe hypertriglyceridemia and is amplified by familial dyslipidemias, diabetes, or metabolic syndrome. Hormonal agents modulate motility and visceral sensitivity, contributing to nausea, bloating, and early satiety; symptom fluctuations may be greater with hormone-free intervals. Epidemiology consistently links combined oral contraceptives to Crohn’s disease in a dose- and duration-dependent fashion. Long-term hormonal therapy can influence GI health via hepatic, lipid, immune, and motility pathways. Absolute risks are low for most users, but individualized counselling, shared decision-making, and targeted monitoring improve safety while preserving therapeutic benefits. Further mechanistic and longitudinal studies are needed to refine risk stratification.